Financing LNG projects and the role of long-term sales-and-purchase agreements - Sophia Ruester (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
The financing of infrastructures is a major topic in recent energy policy debates. Project finance, as a specialized form of debt finance, thereby has become a well-established financing tool. This paper contributes a qualitative and quantitative analysis of the determinants of the debt ratio in project finance, using data on 26 liquefied natural gas (LNG) export and import projects. We argue that lenders will make their decision on how much to lend dependent on the risk profile of the project. In this vein, a project's off-take agreements serve as a security for financial contracts. We empirically show that the debt ratio of an LNG project decreases with increasing risks associated to future cash flows. Estimation results confirmthat leverage increases with higher shares of a project's capacity sold under long-term sales-and-purchase agreements, with a lower capital outlay of the project, and with a lower risk index of the country where the project is located.
Keywords: C21; G32; L22; L95; 330; project finance; debt ratio; long-term contracts; liquefied natural gas